The effect of self-development through peer intercourse on work motivation in Indonesian students: The effect of self-development through peer intercourse on work motivation in Indonesian students - sutarum; Hariono (Journal of diversity in learning (JDIL), 2020)
The purpose of this study was to determine the effect of peer interaction on the lack of work motivation of adolescents. This type of research is descriptive research. The sample in this study were 50 adolescents aged 18-24 years who socialize in the community in Kali village, Pucuk sub-district, Lamongan district. The data analysis used in this research is descriptive analysis. The sampling technique used was the purposive sampling technique. The results showed that peer-to-peer interaction got a score of 2,364 or an average score of 47.28 was categorized as high. Work motivation obtained a score of 2,439 with an average score of 48.78 categorized as high. From the overall results, it can be concluded that there is an effect of peer interaction on adolescent work motivation because good relationships with peers can also increase adolescent work motivation